Determinant of the matrix $$A= \begin{bmatrix}a&b&c\\d&e&f\\g&h&i\end{bmatrix}$$ is $$\det A=4.$$ So what is the determinant of \begin{bmatrix}3a&3b&3c\\-d&-e&-f\\g-a&h-b&i-c\end{bmatrix}

I found that the row operations that were done were $3R1, -1.R2,$ and the last one doesn't matter.

So is the determinant $3\times 4\times(-1)= -12$ or we have to do the inverse $4\times 1/3 \times 1/(-1)?$

  • 3
    $\begingroup$ Yes the answer is -12. Your approach is correct. $\endgroup$ Nov 9 '18 at 17:54

Yes that's correct, indeed by the properties of the determinant we have that

$$\det\begin{bmatrix}a&b&c\\d&e&f\\g&h&i\end{bmatrix}=\det\begin{bmatrix}a&b&c\\d&e&f\\g-a&h-b&i-c\end{bmatrix}=\\=\frac13 \det\begin{bmatrix}3a&3b&3c\\d&e&f\\g-a&h-b&i-c\end{bmatrix}=-\frac13 \det\begin{bmatrix}3a&3b&3c\\-d&-e&-f\\g-a&h-b&i-c\end{bmatrix}$$


Sometimes you can't tell if matrix $B$ can be generated from matrix $B$ or not. In such a case, one may expand each determinant and compare the result of each. However, this approach requires careful attention to signs!

Let $X$ be the determinant of the first matrix and $Y$ be the determinant of the 2nd matrix, then we have:

$ X = a(ei - fh) - b(di - fg) + c(dh - eg) $

$ X = aei - afh - bdi + bfg + cdh - ceg $

$ Y = 3afh - 3eai + 3ecg + 3bdi - 3bfg - 3cdh $

$ \frac{Y}{-3} = -afh + eai -ecg -bdi + bfg + cdh $

You could re-arrange the terms of any of the equations to see that:


Since X=4,



Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.